PENNYWISE AS PROOF OF A BROKEN SYSTEM: SYSTEMIC DYSFUNCTION AND COMMUNAL COMPLICITY IN STEPHEN KING’S IT (World Conference on Social Sciences, Law and Public Policy, 2026)
In most people's minds, Pennywise is a monster - a shape-shifting clown that emerges from the drains of Derry, Maine, every twenty-seven years to devour frightened children. The more disturbing truth of It (1986) is the antithesis of the monstrous spectacle, this paper argues. Pennywise is less the source of Derry’s problems than a manifestation of them. He's the example of the system that has failed the children already. Derry's adults have long learned to avert their gaze, its institutions have learned to forget and its everyday cruelties – bullying, domestic abuse, racism, neglect – have been quietly normalised. It's only because the town has created the environment in which a clown can keep eating that he's so successful.
Keywords: Stephen King, It, Pennywise, systemic dysfunction, structural violence, bystander effect, communal complicity, childhood vulnerability, horror and social critique.